Changes in Anticoagulant Utilization Among United States Nursing Home Residents With Atrial Fibrillation From 2011 to 2016. Issue 9 (7th May 2019) - Alcusky, Matthew; McManus, David D.; Hume, Anne L.; Fisher, Marc; Tjia, Jennifer; Lapane, Kate L.
Abstract : Background: Nursing home residents with atrial fibrillation are at high risk for ischemic stroke and bleeding events. The most recent national estimate (2004) indicated less than one third of this high‐risk population was anticoagulated. Whether direct‐acting oral anticoagulant (DOAC) use has disseminated into nursing homes and increased anticoagulant use is unknown. Methods and Results: A repeated cross‐sectional design was used to estimate the point prevalence of oral anticoagulant use on July 1 and December 31 of calendar years 2011 to 2016 among Medicare fee‐for‐service beneficiaries with atrial fibrillation residing in long‐stay nursing homes. Nursing home residence was determined using Minimum Data Set 3.0 records. Medicare Part D claims for apixaban, dabigatran, edoxaban, rivaroxaban, and warfarin were identified and point prevalence was estimated by determining if the supply from the most recent dispensing covered each point prevalence date. A Cochran‐Armitage test was performed for linear trend in prevalence. On December 31, 2011, 42.3% of 33 959 residents (median age: 85; Q1 79, Q3 90) were treated with an oral anticoagulant, of whom 8.6% used DOACs. The proportion receiving treatment increased to 47.8% of 37 787 residents as of December 31, 2016 ( P <0.01); 48.2% of 18 054 treated residents received DOACs. Demographic and clinical characteristics of residents using DOACs and warfarin were similar in 2016. Half of the 8734 DOAC users received standard dosages and most were treated with apixaban (54.4%) or rivaroxaban (35.8%) in 2016. Conclusions: Increases in anticoagulant use among US nursing home residents with atrial fibrillation coincided with declining warfarin use and increasing DOAC use.